Разделяющее преобразование и неравенства для открытых множеств - Бахтин, А.К.; Вьюн, В.Е. (Видавничий дім "Академперіодика" НАН України, 2007)
The extremal problems of the theory of univalent functions are studied. Some known results concerning the extremal problems with free poles for nonoverlapping domains are extended to the special classes of open sets.